2006
DOI: 10.4049/jimmunol.176.3.1525
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Vaccination of Active Arthritis with a Glycosylated Collagen Type II Peptide in Complex with MHC Class II Molecules

Abstract: In both collagen-induced arthritis (CIA) and rheumatoid arthritis, T cells recognize a galactosylated peptide from type II collagen (CII). In this study, we demonstrate that the CII259–273 peptide, galactosylated at lysine 264, in complex with Aq molecules prevented development of CIA in mice and ameliorated chronic relapsing disease. In contrast, nonglycosylated CII259–273/Aq complexes had no such effect. CIA dependent on other MHC class II molecules (Ar/Er) was also down-regulated, indicating a bystander vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 49 publications
3
72
0
Order By: Relevance
“…This study also demonstrated that the CII 261-273 peptide requires internalization by APC, regardless of DM expression, and that it is presented via class II molecules accessing the recycling pathway. Studies suggest that differential processing of glycosylated versus non-glycosylated CII may reflect crucial differences between RA patients and normal individuals [6,38,39]. It has been shown that CII exists largely in the glycosylated form in healthy cartilage, whereas RA cartilage is characterized by the presence of both glycosylated and non-glycosylated forms of CII [6,7,39].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study also demonstrated that the CII 261-273 peptide requires internalization by APC, regardless of DM expression, and that it is presented via class II molecules accessing the recycling pathway. Studies suggest that differential processing of glycosylated versus non-glycosylated CII may reflect crucial differences between RA patients and normal individuals [6,38,39]. It has been shown that CII exists largely in the glycosylated form in healthy cartilage, whereas RA cartilage is characterized by the presence of both glycosylated and non-glycosylated forms of CII [6,7,39].…”
mentioning
confidence: 99%
“…It has been shown that CII exists largely in the glycosylated form in healthy cartilage, whereas RA cartilage is characterized by the presence of both glycosylated and non-glycosylated forms of CII [6,7,39]. While the posttranslational modification of CII may play a role in the balance between tolerance and autoimmunity in mice and in humans [6,7,38,39], the specific role of T cells against the glycosylated and non-glycosylated CII epitope(s) still remains unclear. APC may also vary in their ability to process and generate distinct pools of glycosylated and non-glycosylated CII, altering antigen processing and T cell responses to the dominant epitope.…”
mentioning
confidence: 99%
“…We have previously shown the importance of galactosylation at position K 264 of CII259-273 for the immune recognition [12][13][14][15][16][17] and that CII in the healthy individuals is completely glycosylated at this position [16]. In line with these findings, an additional modification at position Q 267 by deamidation makes the study of the immune response more complex.…”
Section: Discussionmentioning
confidence: 54%
“…It is well established that during aging, inflammation, trauma or other pathologic processes, the frequency of posttranslational modifications, such as glycosylation, glycation, citrullination, oxidation, deamidation/transamidation or phosphorylation, is increased [10,11]. The role of glycosylated immunodominant CII260-270-peptide for development of autoimmune arthritis has been previously described [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation